New type of multivalued contractions with related results and applications - Işık, H.; Ionescu C. (Politechnica University of Bucharest, 2018)
In this paper, we focus on achieving new results about the existence of fixed points for a new type of multivalued contractions. We furnish an example which demonstrate the supremacy of our results to the existing ones in the literature. We derive new fixed point results on a metric space endowed with a partial ordering/graph by using the results obtained herein. We also discuss sufficient conditions to ensure the existence of solutions of integral equations as an application of our results. © 2018 Politechnica University of Bucharest. All rights reserved.
Keywords: Admissible mapping; Graph; Integral equation; Partial order; ?-?-contraction; ?-contraction